Effectiveness and safety of auricular acupuncture on adjuvant analgesia in patients with total knee arthroplasty: a randomized sham-controlled trial - Zhang, Xingshuo; Chen, Hao; Li, Jingqiao; Liu, Xingang; Wang, Xuesong; Xue, Pingju; Lin, Miao; Li, Jidong; She, Yanfen (Frontiers in Neurology, 2024)
Objective This study aimed to evaluate the effectiveness and safety of auricular acupuncture (AA) on postoperative analgesia, the degree of postoperative nausea, and the effect of inflammation after total knee arthroplasty (TKA). Methods This was a single-center, placebo-controlled, randomized clinical trial. In total, 96 patients were randomly divided into an AA group with an indwelling intradermal needle (n = 48) and a sham auricular acupuncture (SAA) group with a non-penetrating placebo needle (n = 48). Intra-spinal anesthesia was adopted in both groups during surgery, and an epidural analgesic pump was implanted after surgery for 48 h. The primary outcome was the post-surgery visual analog score (VAS) of resting and movement states (at 6, 12 h and 1, 2, 3, 5, and 7 days). The secondary outcomes included additional doses of analgesic injection during the treatment, C-reactive protein (CRP) levels, erythrocyte sedimentation rate (ESR), and white blood cell (WBC) count on the 1st, 3rd, and 7th day after the operation, nausea on the 1st, 2nd, and 3rd day after the operation, the Hospital for Special Surgery Knee Score (HSS) on the 2nd and 12th week after the operation, and adverse events. Results The VAS in the AA group at 6 h, 12 h, 2, 3, and 5 days after surgery were lower than those of the SAA group (p < 0.05). Among the secondary outcomes, the total dose of additional analgesic injection after surgery in the AA group was lower than that in the SAA group (p < 0.05). The serum CRP on the 1st day after operation in the AA group was lower than that in the SAA group (p < 0.05). The degree of nausea on 2nd day after surgery in the AA group was lower than that in the SAA group (p < 0.05). There was no significant difference in other outcomes (p > 0.05). Conclusion In this study, AA was shown to be an effective and safe complementary and alternative therapy for pain relief after TKA, which was able to reduce the total postoperative dose of additional painkillers, decrease serum CRP 1 day after surgery, and improve the degree of postoperative nausea. Clinical trial registration www.chictr.org.cn, ChiCTR2100054403.